CULTURE AS A MEDIATOR OF HEALTH DISPARITIES: CULTURAL CONSONANCE, SOCIAL CLASS, AND HEALTH. Issue 2 (November 2014) - Dressler, William W.; Balieiro, Mauro C.; Ribeiro, Rosane P.; dos Santos, José Ernesto; Leatherman, Thomas
<x xml:space="preserve">Abstract</x> Health disparities or health inequalities refer to enduring differences between population groups in health status, well‐being, and mortality. Health inequalities have been described by race, ethnic group, gender, and social class. A variety of theories have been proposed to account for health inequalities, including access to medical care and absolute material deprivation. Several theorists (including Michael Marmot and Richard Wilkinson) have argued that relative deprivation is the primary factor. By this they mean the inability of individuals to achieve the kind of lifestyle that is valued and considered normative in their social context. In this article, we show that the concept and measurement of cultural consonance can operationalize what Marmot and Wilkinson mean by relative deprivation. Cultural consonance is the degree to which individuals approximate, in their own beliefs and behaviors, the prototypes for belief and behavior encoded in shared cultural models. Widely shared cultural models in society describe what is regarded both as appropriate and desirable in many different domains. These cultural models are both directive and motivating: people try to achieve the goals defined in these models; however, as a result of both social and economic constraints, some individuals are unable to effectively incorporate these cultural goals into their own lives. The result is an enduring loss of coherence in life, because life is not unfolding in the way that it, culturally speaking, "should." The resulting chronic stress is associated with psychobiological distress. We illustrate this process with data collected in urban Brazil. A theory of cultural consonance provides a uniquely biocultural contribution to the understanding of health inequalities.